Factors influencing electronic Government Procurement (e-GP) in Bangladesh - Huda, Md. Nurul (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.